Nilai Edukatif Permainan Tradisional Congklak dalam Mengembangkan Kemampuan Berhitung Siswa Kelas II Sekolah Dasar Negeri 04 Bengalon - Fitri Handayani Sepe; Anjani Putri Belawati Pandianga; Aham Mutasyarifin (Civiliza Publishing, Indonesia., 2026)
This study aimed to analyze the implementation of the educational values of the traditional game congklak in developing students’ counting ability and to identify its advantages and disadvantages at Sekolah Dasar Negeri 04 Bengalon, Bengalon District, East Kutai Regency. A qualitative field research approach was employed. Data were collected through observation, in-depth interviews with one second-grade teacher and three second-grade students, and documentation. The data were analyzed using Miles and Huberman’s interactive model and validated through triangulation techniques. The findings revealed that the traditional game congklak contained significant educational values in developing students’ counting ability, particularly in the cognitive aspect, such as recognizing numbers, counting seeds, and performing simple addition and subtraction. In addition, the game also fostered affective values, including honesty and patience, as well as social values such as cooperation and positive interaction among students. The advantages of using congklak included making learning more enjoyable, improving concentration and learning interest, and preserving local culture. However, several disadvantages were also identified, such as the limited number of players, the need for specific equipment, relatively long playing time, and the requirement for intensive teacher guidance. The study concluded that integrating the traditional game congklak into classroom instruction can serve as an effective and contextual alternative medium for developing both counting skills and character among lower-grade elementary school students